Heterogeneity of Treatment Effects From an Intensive Lifestyle Weight Loss Intervention on Cardiovascular Events in Patients With Type 2 Diabetes: Data From the Look AHEAD Trial - de Vries, Tamar I. (Diabetes Care, 2019)
OBJECTIVE: To explore the presence of heterogeneity of treatment effect (HTE) of an intensive lifestyle intervention on the occurrence of major cardiovascular events (MACE) in overweight or obese patients with type 2 diabetes, and to identify patient characteristics associated with individual treatment effect. RESEARCH DESIGN AND METHODS: In 4,901 participants from the Action for Health in Diabetes (Look AHEAD) trial, a penalized Cox regression model to predict treatment effect of intensive lifestyle intervention for the risk of MACE was derived, including all possible treatment-by-covariate interaction terms. The ability of the model to predict HTE was confirmed by calculating hazard ratios (HRs) and absolute risk change in quartiles of predicted treatment effect, and baseline patient characteristics were compared between quartiles. RESULTS: In quartile 1 of predicted treatment effect, with the highest predicted risk reduction, there was a significant treatment benefit of intensive lifestyle intervention (HR 0.64 [95% CI 0.49–0.83]), whereas there was no effect from treatment in quartiles 2 and 3 (HR 0.81 [95% CI 0.58–1.14] and 1.13 [95% CI 0.80–1.60], respectively) and a detrimental effect in quartile 4 (HR 1.37 [95% CI 1.09–1.73]). Several patient characteristics in demographics, medical history, physical examination, and laboratory values were associated with the level of treatment effect. CONCLUSIONS: This post hoc analysis of the Look AHEAD trial showed that an intensive lifestyle intervention aimed at weight loss may reduce cardiovascular events in selected patients but may have a detrimental treatment effect in others.